SOLUTION OF MIXED PROBLEM OF ELASTICITY THEORY FOR CYLINDRICAL ORTHOTROPIC PLATE IN THE FORM OF RECTANGULAR - Hayrapetian, V. Zh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2000)
This paper presents a solution to a plane elasticity problem for a cylindrically orthotropic rectangular plate with displacements specified on one edge and stresses on the other three. A small physical parameter is introduced, and the stress function is considered in the problem as a power of this parameter. In recurrent boundary value problems, the stress function is represented as a Fourier series. Infinite systems of linear algebraic equations are obtained to determine the expansion coefficients. The solution to the problem for specific parameter values is reduced to numerical results, allowing one to study the nature of the stress distribution near the embedment.